Forest reclamation of fly ash deposit: a field study on appraisal of mycorrhizal inoculation. Issue 2 (1st November 2015) - Sýkorová, Zuzana; Rydlová, Jana; Slavíková, Renata; Ness, Tara; Kohout, Petr; Püschel, David
Abstract : An extensive field trial was established on a fly ash deposit (1) to evaluate whether the inoculation with arbuscular mycorrhizal fungi (AMF) and/or ectomycorrhizal fungi (EcMF) improves growth and survival of 13 planted tree species and (2) to trace the inoculated mycorrhizal fungi in tree roots after one growing season. Molecular methods were applied to characterize AMF and EcMF entering the studied system (inocula, native soil, and roots of nursery seedlings). Biometric parameters and mortality of the trees were recorded and the presence of AMF and EcMF in sampled trees was determined both microscopically and genetically. Mycorrhizal inoculation did not improve survival or growth of any tree species. Most AMF‐host and all EcMF‐host seedlings were highly precolonized already from the nursery. An abundant and diverse AMF community was also found in the field soil. The AMF inoculum taxa partially overlapped with AMF in the native soil and in the precolonized roots. After one season, the only two inoculum‐unique AMF taxa were detected in host species non‐precolonized or only partially precolonized from the nursery. The components of EcMF inoculum were not detected in any sampled tree. After the season, the ectomycorrhizal hosts maintained most of their original EcMF taxa gathered in nursery, some tree species were additionally colonized by EcMF probably originating from the soil. Our results show considerable self‐restoration potential of nature on the target site. Mycorrhizal inoculation thus did not bring any conclusive advantage to the planted trees and seems superfluous for reclamation practice on the fly ash deposit.